BAHAN AJAR FISIKA BUNYI TERINTEGRASI DENGAN BUDAYA MINAHASA MUSIK KOLINTANG - Rende, Jeane; Tulandi, Djeli (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2020)
There are quite a lot of high school physics books available, but contextual teaching materials based on local wisdom are still lacking in schools. Explicitly the 2013 curriculum provides an opportunity for schools and teachers to develop contextual and local wisdom teaching materials but their determination and motivation are still encouraged and encouraged. In increasing the competence and professionalism of alumni as prospective physics teachers, it is necessary to be equipped with experience in designing contextual regional-based teaching materials. Research on the development of teaching materials based on local culture Kolintang music instrument carried out for 6 months. To build competence as a whole and systematically, the focus of research (development of teaching materials) is: (1) determining the main elements in teaching materials namely attitudes (curiosity about natural phenomena), processes (problem solving processes), products (in the form of facts, principles, theory, and law), and contextual (application in everyday life). 2. Studying the previous teaching material to be developed seen from the aspect of breadth, depth, whether or not there is a concept map, a decrease in formulas (mathematical aspects), student worksheets (LKS) to make observations. 3 Testing of teaching materials in schools as a test of the feasibility of using teaching materials. The efficiency and productivity of students increases as reflected in the improvement of their learning achievements. The results showed that the formulation of physical concepts contained in the Kolintang music instrument play are the concepts of momentum and impulse, the concept of vibration, the concept of resonance, the concept of sound waves (longitudinal waves), the concept of sound propagation in the air / gas medium, the concept of period and frequency sound produced by each type of instrument, the concept of sound wave energy and the concept of the intensity of the sound waves produced by kolintang. Physics teaching materials integrated with Minahasa culture Kolintang tools for high schools are suitable for use in schools.